2006
DOI: 10.1021/ma061823x
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific Structure, Degradation, and Functionalization of Polyperoxides Prepared from Sorbic Acid Derivatives with Oxygen

Abstract: We have fabricated degradable polyperoxides (PP) consisting of well-controlled 5,4-repeating units using various sorbic acid derivatives and molecular oxygen by an alternating radical copolymerization process. The PP obtained from the sorbic esters decompose via a radical chain reaction mechanism, leading to the formation of controlled low-molecular-weight products. In contrast, PP from some amide derivatives include an irregular chain structure, resulting in a more complicated degradation behavior. The theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
(37 reference statements)
1
31
0
Order By: Relevance
“…In this so-called homolytic displacement reaction, the peroxide is split into two alkoxyl radicals, one of which forms an epoxide, whereas the other induces cleavage between the carbons bearing the alkoxyl radical and the peroxide group to form the two aldehydes benzaldehyde and formaldehyde in a chain reaction. Related chemistry is characterized with other starting materials (31,32). The overall outcome of carbon chain cleavage of peroxide-linked polymers into aldehydes triggered further interest in the dimerization or oligomerization of fatty acid derivatives during autoxidation.…”
Section: New Insights From Novel Products: Evidence For Intermoleculamentioning
confidence: 99%
“…In this so-called homolytic displacement reaction, the peroxide is split into two alkoxyl radicals, one of which forms an epoxide, whereas the other induces cleavage between the carbons bearing the alkoxyl radical and the peroxide group to form the two aldehydes benzaldehyde and formaldehyde in a chain reaction. Related chemistry is characterized with other starting materials (31,32). The overall outcome of carbon chain cleavage of peroxide-linked polymers into aldehydes triggered further interest in the dimerization or oligomerization of fatty acid derivatives during autoxidation.…”
Section: New Insights From Novel Products: Evidence For Intermoleculamentioning
confidence: 99%
“…Interpolymerization of vinylic monomers with O 2 appears to be quite ubiquitous, as no compound containing the vinyl or vinylidene group has been found which does not readily form a peroxide upon exposure to air under ordinary conditions, which have all been found to initiate polymerization . Kishore et al reported the preparation of oligo(peroxide)s with O 2 of typical vinylic monomers, including nonsubstituted, monosubsttituted, 1,1‐disubstituted (vinylidene), 1,2‐disubstituted vinylics, and conjugated dienes form oligo(peroxide)s under the induction of ultraviolet (UV) light, visible light, heat or radicals, or catalysis of Co II complexes, in bulk or organic solvents, while Matsumoto successfully attempted the radical alternating oxidative polymerization of conjugated dienes with O 2 , leading to degradable poly(peroxide)s …”
Section: Introductionmentioning
confidence: 99%
“…This class of polymers are gaining significant importance due to their applications as polymeric initiators for the radical polymerization of vinyl monomers, autocombustible fuel, dismantlable adhesion, etc. Radical copolymerizations of 1,3‐diene monomers, dibenzofulvene, 7,7,8,8‐tetrakis(ethoxycarbonyl)quinodimethane and related monomers with oxygen have also been carried out to prepare alternating copolymers consisting repeat peroxy units in the polymer backbone. In the literature, most vinyl polyperoxides have been synthesized by 2,2′‐azobisisobutyronitrile (AIBN)‐initiated polymerization of vinyl monomers and oxygen at or above 50 °C .…”
Section: Introductionmentioning
confidence: 99%